Preliminary Study: The Influences of Environmental Management Practices and Customer Satisfaction towards Customer Loyalty - Yusof, Yusnita; Ibrahim, Yahaya; Awang, Zainudin (School of Social Sciences, 2015)
Green hotel is one of the efforts taken towards achieving environmental sustainability through environmental management practices applied in the hotel. However, up until November 2014, there were only 10 out of 1935 hotels registered with the Ministry of Tourism and Culture, Malaysia received ASEAN Green Hotel Award. This study attempts to examine the environmental management practices in non-green hotels, and also the relationship between environmental management practices, customer satisfaction and customer loyalty among guests in a non-green hotel. Respondents were selected using a random sampling technique and data was analysed using SPSS. The findings show that all the environmental management practices have a positive relationship with customer satisfaction and customer loyalty.